The Influence of Indonesia’s National Economic Policy on Human Resource Development in Humbang Hasundutan Regency - Sigit Sugiardi; Franciskus Antonius Alijoyo; B.M.A.S. Anaconda Bangkara; Suslinawati Suslinawati; Ery Niswan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study is motivated by the growing importance of national economic policies in supporting human resource development at the local level, particularly in regions facing geographical limitations and constrained local capacity. The purpose of this research is to examine the influence of Indonesia’s national economic policies on human resource development in Humbang Hasundutan Regency, North Sumatra. A quantitative approach was employed, with data collected through a survey of 223 civil servants working at the local Department of Education. Multiple regression analysis was used to assess the effects of five dimensions of national economic policy, namely infrastructure development, deregulation and investment climate, downstreaming and industrialization, social welfare programs, and economic digitalization. The findings indicate that all five policy dimensions have a positive and significant effect on human resource development, with the combined model explaining 52% of the variance. Infrastructure development and social welfare programs exhibit the strongest individual effects. The study concludes that coordinated and integrated economic policy implementation plays a crucial role in enhancing human resource capacity, while also highlighting contextual challenges related to geographical accessibility, digital inclusion, and limitations in local institutional capacity.